Suprafascial versus traditional harvesting technique for free antero lateral thigh flap: A case‐control study to assess the best functional and aesthetic result in extremity reconstruction. Issue 8 (9th October 2017) - Maruccia, Michele; Fallico, Nefer; Cigna, Emanuele; Ciudad, Pedro; Nicoli, Fabio; Trignano, Emilio; Nacchiero, Eleonora; Giudice, Giuseppe; Ribuffo, Diego; Chen, Hung‐Chi
Abstract : Clinical applications of ALT flap have currently extended to extremity (hand and foot) as well as oral cavity reconstruction. In these anatomical areas, the traditional harvesting technique presents a few disadvantages such as bulkiness of the recipient site and potential donor site morbidity including damage to the deep fascia and skin graft adhesions. The purpose of the present study was to compare the functional and aesthetic outcomes of upper and lower extremity reconstruction with either suprafascial or subfascial harvested anterolateral (ALT) flaps. Sixty patients who underwent hand or foot reconstruction with an ALT flap between January 2013 and January 2015 were included in the study (34 flaps elevated on a subfascial plane and 26 on a suprafascial plane). Group 1 (subfascial harvested ALT flap) was composed of 23 male and 11 female patients with an average age of 53.4 years (range, 36–72 years). Group 2 (suprafascial harvested ALT flap) was composed of 18 male and 8 female patients with an average age of 48.7 years (range, 32–69 years). Surgical indication was tumor resection for 20 patients in group 1 and 16 patients in group 2, chronic ulcer for 8 patients in group 1 and 6 patients in group 2, and trauma for 6 patients in group 1 and 4 patients in group 2. Complications were documented. Aesthetic outcomes were considered in terms of bulkiness of the recipient site, subsequent request for a debulking procedure, and donor site morbidity. Donor site scars were evaluated for cosmesis using a modified Hollander Wound Evaluation Scale (HWES). Skin grafts outcomes were assessed according to the modified Vancouver Scar Scale (VSS). Functional outcome at the recipient site was measured using the Enneking functional outcome score (ESS). Total range of motion (ROM) was recorded. All flaps were successfully elevated with at least one viable perforator with both approaches. The survival rates of suprafascial and subfascial harvested ALT flaps were 96.2 and 97% respectively ( P = .85). The mean flap size was 110.4 ± 27.8 cm 2 in group 1 and 159.7 ± 44.4 cm 2 in group 2. The average flap thickness was 26.2± 5.2 mm in group 1 and 13.9 mm ± 4.1 in group 2. Complications included total flap loss (1 case in group 1 and 1 case in group 2), partial flap loss (2 cases in group 1 and 1 case in group 2), skin graft failure (3 cases in group 1), and muscle herniation at the donor site (1 case in group 1; P < .17). Secondary debulking procedures were needed for 20 flaps in the subfascial group and for one flap in the suprafascial group ( P ‐value <.01). Donor site closure with skin grafts was necessary in 42 cases: 32 in group 1 and 10 in group 2. The suprafascial harvested ALT flap group reported a significant difference in terms of donor site morbidity. The HWES score of donor site scars was significantly lower in group 1 (mean 1.2 ± 0.54) than in group 2 (mean 2.4 ± 0.58), P < .01. Similarly, the VSS score for skin graft outcomes was lower in patients of group 1 (mean 4.5 ± 0.93) than in patients of group 2 (mean 6.7 ± 0.96), P < .01. There was also a significant lower score of postoperative ESS in patients of group 1 (mean 21.2 ± 3.4) when compared with patients of group 2 (mean 23.6 ± 2.7), P < .01. Total ROM improved on average 60° after surgery ( P ‐value <.01). The suprafascial plane for elevating ALT flaps presented several advantages over the traditional subfascial approach in terms of functional and aesthetic outcomes, providing a thin flap allowing increased versatility to achieve better contour of flap, and minimizing the need for secondary debulking.